2008
DOI: 10.1007/s11258-008-9556-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term signals of climate change along an altitudinal gradient in the South Alps

Abstract: Short-term changes in plant species number, frequency and composition were studied along an altitudinal gradient crossing four summits from the treeline ecotone to the subnival zone in the South Alps (Dolomites, Italy). Large-scale (summit areas) and small-scale patterns (16 plots of 1 m 2 /summit) were monitored. After 5 years, a re-visitation of the summit areas revealed a considerable increase of species richness at the upper alpine and subnival zone (10% and 9%, respectively) and relatively modest increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 54 publications
10
57
0
2
Order By: Relevance
“…However, the conditions at the study summits in the Alps and at the study summits at Dovrefjell are difficult to compare. For instance, the total number of vascular species at most of the summits analyzed by Erschbamer et al [26] is much higher than at the study summits at Dovrefjell.…”
Section: Changes With Respect To Summitmentioning
confidence: 71%
See 3 more Smart Citations
“…However, the conditions at the study summits in the Alps and at the study summits at Dovrefjell are difficult to compare. For instance, the total number of vascular species at most of the summits analyzed by Erschbamer et al [26] is much higher than at the study summits at Dovrefjell.…”
Section: Changes With Respect To Summitmentioning
confidence: 71%
“…In similar studies from the Alps, the largest increase in species richness was found in the upper alpine and subnival zone [26] and in the subnival/nival zone [13]. Erschbamer et al [26] even found that the species richness decreased at the lower summits.…”
Section: Changes With Respect To Summitmentioning
confidence: 86%
See 2 more Smart Citations
“…Many studies have investigated vegetation types and patterns along altitudinal gradients in the mountains (Kitayama, 1992;Lovett, 1996;Kessler, 2000;Hemp, 2006). The three-dimensional pattern of vegetation landscapes are usually been related to the species diversity and distribution (Körner, 2000;Kitayama and Aiba, 2002;Wang el al., 2002;Bhattarai and Vetaas, 2003;Wang et al, 2007;Batllori et al, 2009;Sang, 2009 (Daniels and Veblen, 2003;Gian-Reto et al, 2005;Walther et al, 2005;Erschbamer et al, 2009;Odland, 2009;Wang et al, 2009). Identifying the three-dimensional pattern of vegetation landscapes could improve their ecological interpretation (Kitayama, 1992;Miehe, 1994;Fang et al, 1996;Tang and Ohsawa, 1997;Leuschner, 2000;Hörsch, 2003;Tang, 2006;Proctor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%